2004
DOI: 10.1021/bi0495073
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Substrate Selective p38α Inhibitor

Abstract: A novel inhibitor of p38 mitogen-activated protein kinase (p38), CMPD1, identified by high-throughput screening, is characterized herein. Unlike the p38 inhibitors described previously, this inhibitor is substrate selective and noncompetitive with ATP. In steady-state kinetics experiments, CMPD1 was observed to prevent the p38alpha-dependent phosphorylation (K(i)(app) = 330 nM) of the splice variant of mitogen-activated protein kinase-activated protein kinase 2 (MK2a) that contains a docking domain for p38alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 42 publications
1
87
2
Order By: Relevance
“…The MAP kinase-activated protein kinase MK2 is a strong candidate for ERK-dependent post-transcriptional regulation of mRNA levels and has been previously implicated in the regulation of TNF-a and IL-6 mRNA levels in macrophages [42][43][44][45]. Consistent with this hypothesis, the specific MK2a inhibitor, CMPD1 [46], significantly decreased IL-2 but not IL-10 mRNA levels (Supporting Information Fig. 1).…”
Section: Il-10 Production Requires Transcription But Is C-fos Indepensupporting
confidence: 58%
“…The MAP kinase-activated protein kinase MK2 is a strong candidate for ERK-dependent post-transcriptional regulation of mRNA levels and has been previously implicated in the regulation of TNF-a and IL-6 mRNA levels in macrophages [42][43][44][45]. Consistent with this hypothesis, the specific MK2a inhibitor, CMPD1 [46], significantly decreased IL-2 but not IL-10 mRNA levels (Supporting Information Fig. 1).…”
Section: Il-10 Production Requires Transcription But Is C-fos Indepensupporting
confidence: 58%
“…A peptide inhibitor of cyclin-dependent kinase-mediated Rb phosphorylation has been developed that does not affect cyclin-dependent kinase-mediated histone phosphorylation (78). CMPD1 is a small molecule inhibitor of p38␣ MAPK that exhibits substrate-selective inhibition of MK2 versus ATF-2 (79). In addition, the finding that the FXFP-site binds to a different part of the MAPK surface than the D-site (35) suggests that it should be possible to specifically inhibit FXFP interactions.…”
Section: Discussionmentioning
confidence: 99%
“…showed that targeting the non-ATP binding site of a MAP kinase could produce a substrate selective inhibitor [99]. They discovered a non-ATP p38 MAPKα inhibitor (16) that inhibits the phosphorylation of MK2a with a K i of ~330 nM.…”
Section: Small Molecules Targeting the Drs Of P38 Mapk-in 2004 Davidmentioning
confidence: 99%
“…Isothermal titration calorimetry analysis confirmed the binding of 16 to p38 MAPKα, but showed that this compound does not prevent the binding of MK2a. While a deuterium exchange mass spectrometry (DXMS) study suggested that 16 binds in the vicinity of the p38 MAPKα active site and disrupts the ATP binding site [99], the basis for its substrate selectivity is unknown.…”
Section: Small Molecules Targeting the Drs Of P38 Mapk-in 2004 Davidmentioning
confidence: 99%